On the Conceptions of the History of Lithuania at the Old Vilnius University - Šidlauskas, Algirdas (Problemos, 1972)
The present article deals with the works on the history of Lithuania by J. Kojelavičius (J. Koialowicz), J. Lelewel, J. Onacevicius (J. Onacewicz) and J. Danilavičius (J. Danilowicz). The endeavour of the above authors to get rid of various legends interwoven with historical facts as well as their work in collecting historic sources, studying and evaluating them, are reviewed. The services of the above historians are found in a more accurate definition of the old sources as well as in stimulating the public’s interest for studying the past of Lithuania.